Deconstructing Peace Through the Human Needs Theory on The Protracted Mozambique Conflict - Humaira, Salsabila; Habibillah, Dhafin Mufid; Dermawan, Windy; Akim (Universitas Cenderawasih, 2026)
Despite being hailed as a post-conflict success story following the 1992 Rome General Peace Accords, Mozambique has relapsed into recurring cycles of violence, including the recent insurgency in Cabo Delgado. This study investigated the fragility of this peace construction by analyzing the structural causes of conflict through the lens of John Burton’s Need-Based Conflict Theory (1991). Adopting a Systematic Literature Analysis (SLA) based on PRISMA guidelines, the research synthesizes findings from ten key academic articles published between 2020–2025. The analysis reveals that post-war stability was merely a negative peace characterized by elite settlements that failed to address non-negotiable human needs. Specifically, the findings highlight critical deficits in four dimensions, distributive justice due to elite resource capture; identity suppressed by hegemonic national narratives; security biased toward strategic assets over human safety; and recognition denied to victims and marginalized groups. The study concludes that sustainable peace in Mozambique requires a paradigm shift from managerial conflict settlement to structural conflict resolution that satisfies these fundamental ontological needs, particularly regarding economic fairness and cultural inclusion. KEYWORDSConflict Resolution; Distributive Justice; Human Needs Theory (HNT); Mozambique